Exosomal Transfer of DNA Methyl-Transferase mRNA Induces an Immunosuppressive Phenotype in Human Monocytes. Issue 6 (June 2022) - Wisler, Jon R.; Singh, Kanhaiya; McCarty, Adara; Harkless, Ryan; Karpurapu, Manjula; Hernandez, Edward; Mukherjee, Debasmita; Abouhashem, Ahmed S.; Christman, John W.; Sen, Chandan K.
ABSTRACT: Introduction: Survivors of sepsis exhibit persistent immunosuppression. Epigenetic events may be responsible for some of these immunosuppressive changes. During sepsis circulating exosomes contain large quantities of DNA methyltransferase (DNMT) mRNAs. We hypothesized that exosomes directly transfer DNMT mRNAs to recipient monocytes with resultant methylation events and immunosuppression. Methods: Exosomes containing DNMT mRNA were generated by stimulating monocytes with LPS. Confocal microscopy was used to determine uptake kinetics in the presence of pharmacologic inhibition. Expression and packaging of specific DNMT mRNA was controlled using DNMT siRNAs. Whole genome and gene specific methylation was assessed using bisulfite sequencing. Ingenuity pathway analysis was performed to determine the biological function of significance of differentially methylated regions. Results: Exosomes effectively transferred DNMT mRNA to recipient monocytes. Pharmacologic inhibition of exosome uptake prevented this increase in DNMT mRNA expression. Recipient monocytes exhibited hypermethylation changes and gene suppression. siRNAs decreased the packaging of DNMT mRNAs and prevented TNFα gene suppression, restoring immunocompetence. Conclusion: These data support a role for exosome-mediated transfer of DNMT mRNA with resultant methylation and gene silencing. Pharmacologic uptake inhibition or targeted siRNA mediated DNMT gene silencing prevented DNMT mRNA transfer and maintained the cell's ability to express TNFα in response to LPS. This highlights the potential therapeutic value of targeting these exosome-mediated epigenetic events to maintain the host immune response during sepsis.